Estimation of Elasticities of Substitution for CES and VES Production Functions using Firm-level Data for Food-processing Industries in Pakistan (The Pakistan Development Review, 1988)
This study, based on the time-series data covering the period from 1956 to 1986, estimates production function in the agricultural sector of Pakistan. The strategy for agricultural development in the country has been based on greater utilization of "high pay-off' low-cost technology. The government advanced loans through financial institutions to make it possible for the farmers to acquire this technology. Despite the infusion of seed-fertilizer technology, per acre yield of major crops like wheat, rice, cereal and sugar-cane in Pakistan is lower than in most LDCs in the region. Therefore, it is concluded that the use of present technology has reached a plateau and it is time to look for additional inputs for improvement in productivity.